Development of spin‐contrast‐variation neutron reflectometry for the structural analysis of multilayer films. Issue 5 (6th September 2019) - Kumada, Takayuki; Akutsu, Kazuhiro; Ohishi, Kazuki; Morikawa, Toshiaki; Kawamura, Yukihiko; Sahara, Masae; Suzuki, Jun-ichi; Torikai, Naoya
Abstract : The reflectivity curves of polarized neutrons vary strongly as a function of the proton polarization of the film samples. It is demonstrated that detailed structural information on each surface and interface of a multilayer film sample can be obtained from these proton‐polarization‐dependent multiple reflectivity curves. Abstract : The spin‐contrast‐variation neutron reflectometry technique was developed for the structural analysis of multilayer films. Polarized‐neutron reflectivity curves of film samples vary as a function of their proton polarization ( P H ). The P H ‐dependent reflectivity curves of a polystyrene monolayer film were precisely reproduced using a common set of structural parameters and the P H ‐dependent neutron scattering length density of polystyrene. This result ensures that these curves are not deformed by inhomogeneous P H but can be used for structural analysis. Unpolarized reflectivity curves of poly(styrene‐ block ‐isoprene) films were reproduced using a flat free‐surface model but P H ‐dependent polarized reflectivity curves were not. The global fit of the P H ‐dependent multiple reflectivity curves revealed that holes with a depth corresponding to one period of the periodic lamellae of microphase‐separated polystyrene and polyisoprene domains were produced on the surface of the films, which agrees with the microscopic results. In this manner, the spin‐contrast‐variation neutron reflectometry technique determines the structure of multiple surfaces and interfaces in a film sample while excluding the incorrect structure that accidentally accounts for a single unpolarized reflectivity curve only.